1999
DOI: 10.2114/jpa.18.225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mental Task on Heart Rate Variability during Graded Head-Up Tilt.

Abstract: Abstract. In this study, we used spectral analysis of heart rate variability (HRV) to estimate the changes in autonomic control in response to disparate stimuli produced by mental task and graded head-up tilting. The low frequency (LF) component of HRV provided a quantitative index of the sympathetic and parasympathetic (vagal) activities controlling the heart rate (HR), while the high frequency (HF) component of HRV provided an index of the vagal tone. We studied 17 healthy male subjects (21-25 yr of age) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…LF is often interpreted as an index influenced by both sympathetic and parasympathetic activity. However, it has been reported that the LF response could vary according to different postures from the supine to the upright position (Ishibashi et al, 1999). One of the most frequently cited papers on HRV (Pomeranz et al, 1985) points out that the vagal blockade by intravenous administration of atropine in a supine subject is also capable of reducing LF by 84%; it was concluded that in this posture, the LF is mediated entirely by the parasympathetic system.…”
Section: Discussionmentioning
confidence: 99%
“…LF is often interpreted as an index influenced by both sympathetic and parasympathetic activity. However, it has been reported that the LF response could vary according to different postures from the supine to the upright position (Ishibashi et al, 1999). One of the most frequently cited papers on HRV (Pomeranz et al, 1985) points out that the vagal blockade by intravenous administration of atropine in a supine subject is also capable of reducing LF by 84%; it was concluded that in this posture, the LF is mediated entirely by the parasympathetic system.…”
Section: Discussionmentioning
confidence: 99%
“…From the ECG monitoring, heart rate (HR) and heart rate variability (HRV) were derived. Many studies have reported the reliability of HRV as a noninvasive index of ANS activity (Ishibashi et al, 1999;Miyatsuji et al, 2002). The high frequencies (HF) of HRV relate to parasympathetic activity, while the low frequencies (LF) of HRV are associated with both parasympathetic and sympathetic activities (Pomeranz et al, 1985).…”
Section: Measurements Of Physiological Indexesmentioning
confidence: 99%
“…Measured items: The following items, verified by the prior study [5][6], were adopted: (1)subjective assessment of fatigue (SAF) through questionnaires (provided by the Japan Society for Occupational Health) and interviews, (2)blinking rate,(3) amplitude rates of differential calculus wave patterns for blinking,(4)heart rate variability (level of sympathetic nerve activity: LF/HF (LF/HF is defined by the ratio of the low frequency band (LF: 0.04-0.15 Hz) and the high frequency band (HF: 0.15-0.5 Hz), calculated by employing FFT analysis using the R-R interval based on heart rate variability obtained from the electrocardiogram [7] [8]), and (5) task performance(rates of correct answers. )…”
Section: A Methodsmentioning
confidence: 99%